Trend of thyroid cancer incidence in China, 1992-2021: a Joinpoint regression and age-period-cohort analysis - XIONG Dan; SU Xiaojun; FANG Yanmei (陆军军医大学学报)
‍Objective‍　‍To analyze the temporal trend of thyroid cancer incidence in China from 1992 to 2021 and evaluate the impact of age, period and cohort on the incidence. Methods‍　‍Based on the Global Burden of Disease 2021, the trend changes of age-standardized incidence rate (ASIR) of thyroid cancer in China from the period were analyzed, and the obtained data were further analyzed with Joinpoint regression and age-period-cohort analysis. Auto regressive integrated moving average (ARIMA) model was applied to predict the incidence of thyroid cancer in China in the next 20 years. Results‍　‍The ASIR of thyroid cancer among males was increased from 0.70/100 000 to 2.11/100 000 between 1992 and 2021, with an average annual percent change (AAPC) of 3.93% (95%CI: 3.86%~4.00%, P<0.001); For the females, the ASIR was elevated from 1.91/100 000 to 2.87/100 000 in the time, with an AAPC of 1.43% (95%CI: 1.36%~1.50%, P<0.001). On the age effect, the overall variation in ASIR among the females was minor, and that in the males reached its peak in the ≥85-years-old group, with a rate of 230.51/100 000. Regarding the period effect, the risk of thyroid cancer incidence in the males and females changed with the period and exhibited a temporal increase, and the incidence risk was consistently higher in the males than the females across different periods. Taking the incidence risk during 1992 and 1996 as a reference (RR=1), the males (RR=2.94, 95%CI: 2.78~3.11) and the females (RR=1.37, 95%CI: 1.32~1.42) had the highest risk of thyroid cancer in the period from 2017 to 2021. On the cohort effect, the risk of thyroid cancer in both sexes showed an increasing trend with cohort change. When taking the cohort during 1992 and 1996 as a reference (RR=1), the females in the pre-1986 cohort exhibited a higher risk of incidence than the males, but in the post-1996 cohort, the males demonstrated a greater risk of incidence than the females. The males in the 2012-2016 cohort had the highest risk of thyroid cancer when compared to the reference group (RR=2.54, 95%CI: 1.80~3.57), and the females in the cohort from 1992 to 2016 had higher risk of thyroid cancer than the reference group, though no statistical differences were observed. The ARIMA model prediction analysis found that the ASIR of thyroid cancer in males and females in China would continue to increase from 2022 to 2041, and the ASIR of thyroid cancer in males would reach 2.79/100 000 (95% CI: 1.96~3.61), and the ASIR of thyroid cancer in females would reach 3.54/100 000 (95% CI: 3.02~4.06) by 2041.Conclusion‍　‍Between 1992 and 2021, the ASIR of thyroid cancer in China has exhibited a consistent upward trend, with the females having a higher ASIR than the males. However, the risk of developing thyroid cancer is higher in men who are older and those who were born more recently. In the next 20 years, the incidence of thyroid cancer among both men and women in China is projected to continue to rise, and the situation for prevention and control will be challenging.